Lithium-substituted sodium oxyvanadophosphate material, and preparation method and application thereof

CN122916178APending Publication Date: 2026-10-16GUANGDONG UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611290785.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-25
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

然而,NVOPF的实际应用受到许多固有挑战的阻碍,包括本征电子电导率低和Na+扩散动力学缓慢等

Benefits of technology

本发明以乙酰丙酮氧钒作为钒源,氟化钠作为钠源和氟源,磷酸二氢铵作为磷酸根源,氟化锂作为取代源;先将乙酰丙酮氧钒溶于乙醇中,另将磷酸二氢铵、氟化钠和氟化锂溶于水中,再将两种溶液合并,经微波水热反应制得反应前驱体,最后将前驱体置于惰性气体氛围下进行热处理,制得无碳包覆的锂取代氟磷酸氧钒钠(NVOPF-Lix)材料。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122916178A_ABST
    Figure CN122916178A_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of sodium ion batteries, and particularly relates to a lithium-substituted fluorophosphovanadyl sodium material and a preparation method and application thereof. The application takes vanadyl acetylacetonate as a vanadium source, sodium fluoride as a sodium source and a fluorine source, ammonium dihydrogen phosphate as a phosphate source, and lithium fluoride as a substitution source; the vanadyl acetylacetonate is first dissolved in ethanol, the ammonium dihydrogen phosphate, the sodium fluoride and the lithium fluoride are then dissolved in water, the two solutions are combined, a reaction precursor is prepared through microwave hydrothermal reaction, and finally the precursor is placed in an inert gas atmosphere for heat treatment to prepare a carbon-free coated lithium-substituted fluorophosphovanadyl sodium (NVOPF-Li x ) material. The lithium is substituted on the sodium site of the NVOPF, so that the electronic conductivity and Na + diffusion rate of the material are further improved, and the material is applied to a sodium ion battery, so that excellent rate performance, long cycle performance and sodium storage capacity can be obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of sodium-ion battery technology, specifically relating to a lithium-substituted sodium vanadium fluorophosphate material, its preparation method, and its application. Background Technology

[0002] Sodium's abundance, uniform distribution, and low cost in the Earth's crust have driven the development of sodium-ion batteries, making them a key candidate technology for large-scale energy storage. However, compared to lithium-ion batteries, sodium-ion batteries currently face bottlenecks such as low energy and power density, limited rate performance, and short cycle life, hindering their industrial application. Fast charging technology can, to some extent, compensate for the inherent energy density limitations of sodium-ion batteries in both large-scale energy storage and low-speed electric transportation applications. Therefore, improving the rate performance of these batteries has become a major focus. Consequently, the development of cathode materials that combine high power output, excellent rate performance, and long-term cycle stability has become an urgent need.

[0003] Among many cathode materials, Na3(VO 0.8 PO4)2F 1.4 (NVOPF) has emerged as a highly promising candidate, with a theoretical capacity of approximately 130 mAh·g. -1 The average operating voltage is as high as approximately 3.8 V (vs. Na). + / Na), can provide up to approximately 500 Wh·kg -1 Its high energy density makes it a viable alternative to commercially available LiFePO4 batteries in certain situations. (Contributed by V2O) 10 A stable three-dimensional framework composed of F-dioctahedrons and PO4 tetrahedra gives it a two-dimensional Na+ structure within the ab plane. + Migration channels. However, the practical application of NVOPFs is hindered by many inherent challenges, including low intrinsic electronic conductivity and Na+. + Slow diffusion kinetics, etc. Current research largely focuses on doping transition metal ion sites with cations to improve the electrochemical performance of NVOPFs; however, this method has limitations, such as... + Compared to the surrounding anions, the vanadium center is more sensitive to Na+. + The migration effect is very limited, while adjusting the anion sites of the framework may introduce impurity phases, thereby impairing the inherent chemical stability of the material.

[0004] Meanwhile, Na in NVOPF + The diffusion of Na+ is affected by the strong electrostatic interaction between Na+ and surrounding anions, as well as Na+. + The combined constraints of dynamic ordering effects and other factors contribute to a high ion migration energy barrier. Therefore, targeted modulation of the sodium sites in the NVOPF is needed to improve its diffusion kinetics. Given that Li...+ The radius (0.76 Å) is smaller than that of Na. + With a radius of 1.02 Å and similar physicochemical properties to sodium and lithium, lithium can be readily doped into the NVOPF lattice without inducing a significant phase transition. Therefore, replacing sodium sites in NVOPF with lithium is the preferred solution to address this key issue. Lithium substitution can both improve the intrinsic electronic conductivity of the material and improve the performance of Na+. + This invention aims to optimize the rate performance of NVOPF by studying diffusion kinetics. Summary of the Invention

[0005] To overcome the shortcomings of the prior art, this invention employs a microwave hydrothermal assisted calcination method that is rapid, low-cost, and scalable, to substitute lithium metal at the Na site, thereby obtaining lithium-substituted vanadium fluorophosphate (NVOPF-Li). x This invention further improves the electronic conductivity and Na+ of the material by replacing the sodium sites of NVOPF with lithium. + The diffusion rate allows this material to achieve excellent rate performance, long cycle life, and sodium storage capacity when used in sodium-ion batteries.

[0006] To achieve the above objectives, the technical solution adopted by the present invention is as follows: The first aspect of this invention provides a method for preparing lithium-substituted sodium vanadium fluorophosphate, the method comprising the following steps: S1. Vanadium acetylacetonate is dissolved in ethanol to prepare a vanadium acetylacetonate solution. Sodium dihydrogen phosphate, sodium fluoride, and lithium fluoride are dissolved in water to prepare a mixed solution. The two solutions are then combined to obtain a premixed solution. The mass ratio of vanadium acetylacetonate to ammonium dihydrogen phosphate, sodium fluoride, and lithium fluoride is 175-195:110-130:49.1-x:x, where 0 < x ≤ 1.00. S2. After the premixed liquid of S1 is subjected to microwave hydrothermal reaction, the obtained reaction precursor is placed in an inert gas atmosphere for heat treatment to obtain lithium-substituted sodium vanadium fluorophosphate material.

[0007] The microwave hydrothermal method employed in this invention effectively solves the problems of long production time, high noise, low yield, and low heat conversion efficiency associated with traditional hydrothermal methods. This is because the microwave hydrothermal method offers advantages such as mild conditions, low energy consumption, fast reaction speed (short reaction time), small product particle size, uniform distribution, minimal particle agglomeration, good crystal morphology, and controllability. Furthermore, replacing the sodium sites in the NVOPF with lithium can further improve the material's electronic conductivity and Na+. + Diffusion rate.

[0008] Preferably, the mass ratio of the vanadium oxyacetylacetonate to ammonium dihydrogen phosphate, sodium fluoride, and lithium fluoride is 180-190:116-125:49.1-x:x, where x=0.5. In this case, the resulting lithium-substituted sodium vanadium oxyacetylacetonate is NVOPF-Li. 0.50 NVOPF-Li possessing micro / nano-scale structure (micro / nano-morphology) 0.50 The particles combine high compaction density, rapid sodium ion transport kinetics, and good structural stability, exhibiting optimal rate performance and long-cycle performance, and possessing the best sodium storage capacity.

[0009] Preferably, the microwave hydrothermal reaction is carried out by heating to 120-140°C at a heating rate of 7-13°C / min under a microwave power of 300-500 W, and reacting at this temperature for 1-3 hours.

[0010] Preferably, the heat treatment temperature is 500-700℃ and the time is 6-8h.

[0011] Preferably, the microwave hydrothermal reaction is carried out under continuous stirring at a speed of 200-400 r / min.

[0012] Preferably, after the microwave hydrothermal reaction, the process further includes washing and drying steps; the washing involves centrifuging the reaction product with water and ethanol respectively to remove impurities; and the drying involves drying the centrifuged precipitate.

[0013] More preferably, the centrifugal cleaning speed is not less than 6000 r / min, preferably 6000-8000 r / min.

[0014] The second aspect of the present invention also provides a lithium-substituted sodium vanadium fluorophosphate material prepared by the preparation method described in the first aspect.

[0015] The third aspect of the present invention also provides the application of the lithium-substituted sodium vanadium fluorophosphate material described in the second aspect as a positive electrode active material in the preparation of sodium-ion batteries.

[0016] Preferably, the method for using the lithium-substituted sodium fluorophosphate vanadium oxyfluoride material to prepare a sodium-ion battery is as follows: the lithium-substituted sodium fluorophosphate vanadium oxyfluoride material, conductive agent and binder are ground and mixed in a mass ratio of 6-8:1-3:0.5-1.5, a solvent is added to the mixture to prepare an electrode slurry with uniform viscosity; the slurry is uniformly coated on a conductive current collector to obtain a positive electrode, a sodium-based negative electrode is used, and sodium-ion battery electrolyte is injected to assemble a coin cell sodium-ion battery.

[0017] More preferably, the conductive agent includes conductive carbon black, the binder includes sodium carboxymethyl cellulose, the solvent includes water, the current collector includes carbon-coated aluminum foil, the sodium-based negative electrode includes metallic sodium, and the electrolyte is a 0.8-1.2M NaPF6 diethylene glycol dimethyl ether solution.

[0018] Compared with the prior art, the beneficial effects of the present invention are: This invention uses vanadium acetylacetonate as the vanadium source, sodium fluoride as the sodium and fluorine sources, ammonium dihydrogen phosphate as the phosphate source, and lithium fluoride as the substitution source. First, vanadium acetylacetonate is dissolved in ethanol, while ammonium dihydrogen phosphate, sodium fluoride, and lithium fluoride are dissolved in water. The two solutions are then combined and subjected to a microwave hydrothermal reaction to obtain a reaction precursor. Finally, the precursor is heat-treated under an inert gas atmosphere to obtain carbon-free lithium-substituted vanadium fluorophosphate (NVOPF-Li). x )Material.

[0019] NVOPF-Li prepared by this method x In this material, as the lithium substitution level increases, a continuous structural phase transition occurs, covering the entire composition range. Simultaneously, the lithium occupancy behavior changes significantly: under low lithium substitution conditions, lithium ions preferentially occupy Na1 sites, while under high lithium substitution, they further occupy Na2 sites. Lithium substitution can also modulate the sample surface morphology, resulting in significant morphological evolution and particle size differences. Therefore, this invention further enhances the electronic conductivity and Na+ of the material by substituting lithium at the sodium sites of the NVOPF. + The diffusion rate allows this material to be applied to sodium-ion batteries, resulting in excellent rate performance, long cycle life, and sodium storage capacity. Attached Figure Description

[0020] Figure 1 NVOPF-Li under different lithium substitution amounts x X-ray diffraction pattern; Figure 2 The refined neutron diffraction pattern for NVOPF; Figure 3 For NVOPF-Li 0.50 The refined neutron diffraction pattern; Figure 4 For NVOPF-Li 1.00 The refined neutron diffraction pattern; Figure 5 The image shows a scanning electron microscope (SEM) image of the NVOPF. Figure 6 For NVOPF-Li 0.50 Scanning electron microscope image; Figure 7 For NVOPF-Li 1.00 Scanning electron microscope image; Figure 8 For NVOPF, NVOPF-Li 0.50 and NVOPF-Li 1.00 Constant current charge-discharge curve at a current density of 1C; Figure 9 For NVOPF, NVOPF-Li 0.50 and NVOPF-Li 1.00 Rate performance at current densities of 1-100C; Figure 10 For NVOPF, NVOPF-Li 0.50 and NVOPF-Li 1.00 Cyclic stability plot at a current density of 20C. Detailed Implementation

[0021] The specific embodiments of the present invention will be further described below. It should be noted that these descriptions are for the purpose of aiding understanding the present invention, but do not constitute a limitation thereof. Furthermore, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.

[0022] Unless otherwise specified, the experimental methods used in the following embodiments are conventional methods, and the experimental materials used in the following embodiments are all available through conventional commercial channels.

[0023] This invention uses vanadium oxyacetylacetonate as the vanadium source, sodium fluoride as the sodium and fluorine source, ammonium dihydrogen phosphate as the phosphate source, and lithium fluoride as the substitution source. The above raw materials are mixed and rapidly reacted via microwave hydrothermal method to form a reaction precursor. Finally, the precursor is further calcined at high temperature under inert gas conditions to obtain carbon-free lithium-substituted vanadium oxyfluorophosphate (NVOPF-Li). x Materials. With increasing lithium substitution, NVOPF-Li x The structure underwent a gradual phase transition, which spanned the entire composition range. Further refinement of NVOPF and NVOPF-Li was achieved through neutron diffraction. 0.50 and NVOPF-Li 1.00 Further structural analysis of the three materials revealed significant changes in lithium occupancy. At low lithium substitution levels, lithium initially occupied Na1 sites, while at high lithium substitution levels, it further occupied Na2 sites. Lithium substitution also modulated the surface morphology of the samples, exhibiting a clear morphological evolution process and particle size differences. Among them, NVOPF-Li, which simultaneously possesses micro- and nano-sized structures, showed a notable variation. 0.50 The particles possess both high compaction density and rapid Na content. + Its transmission dynamics and excellent structural stability demonstrate outstanding rate performance and long-cycle performance.

[0024] To fully and clearly present the technical solution and significant advantages of the present invention, the present invention will be described in detail below with reference to specific embodiments.

[0025] Example: Different lithium-substituted sodium vanadium fluorophosphate (NVOPF-Li) x Preparation of sodium-ion batteries and its application as a cathode material for sodium-ion batteries (1) Dissolve 185.6 mg of acetylacetonate vanadyl in 24 mL of anhydrous ethanol and stir at 200 r / min for 20 min at room temperature to obtain a uniform acetylacetonate vanadyl solution. (2) Dissolve 120.8 mg ammonium dihydrogen phosphate, 49.1-x mg sodium fluoride and x mg lithium fluoride (x=0, 0.25, 0.50, 0.75, 1.00, 1.50, 2.00 or 3.00) in 30 mL of deionized water and stir at 200 r / min for 20 min at room temperature to obtain a mixed solution; (3) Mix the acetylacetone vanadium oxide solution obtained in step (1) and the mixed solution obtained in step (2), and continue to stir at 200 r / min for 30 min at room temperature to obtain a premixed solution; (4) The mixed solution containing vanadium acetylacetonate, sodium dihydrogen phosphate, sodium fluoride and lithium fluoride obtained in step (3) was placed in a microwave hydrothermal reactor. The microwave power of the microwave hydrothermal reactor was set to 400 W and the heating rate was 10 °C / min. After heating to 130 °C, the reaction was carried out at this temperature for 1 h. During the reaction, the reaction system was continuously stirred at 300 r / min. (5) The product of microwave hydrothermal reaction was centrifuged three times each with deionized water and anhydrous ethanol at 6000 r / min to remove impurities. The centrifuged precipitate was dried at 60℃ for 10 h to obtain the reaction precursor. (6) The reaction precursor is placed in a tube furnace and heat-treated at 600°C for 7 hours under an argon atmosphere to obtain sodium vanadium fluorophosphate (NVOPF-Li) with different lithium substitution. x )Material.

[0026] Figure 1 The series of carbon-free lithium-substituted sodium vanadium fluorophosphate (NVOPF-Li) prepared in this embodiment x XRD diffraction patterns of the material. With increasing lithium substitution, NVOPF-Li... x The structure undergoes a gradual phase transition, and this phase transition spans the entire composition range. For NVOPF-Li... x(0 ≤ x ≤ 0.50), its main diffraction peaks can be completely attributed to the tetragonal phase Na3(VOPO4)2F (PDF#97-024-5125, space group: I4 / mmm), indicating that low-level Li substitution does not disrupt the main structure. In contrast, when 0.50 < x ≤ 1.00, the sample exhibits a two-phase mixture of tetragonal Na3(VOPO4)2F and trace amounts of monoclinic Na3V2(PO4)3 (PDF#97-024-8140, space group: R-3c). With further increases in Li content (1.00 < x ≤ 3.00), new lithium-containing phases such as Li3PO4 (PDF#97-002-0208) and LiF (PDF#97-001-8012) begin to appear and gradually become dominant.

[0027] Figure 2-4 The NVOPF and NVOPF-Li prepared in this embodiment 0.50 and NVOPF-Li 1.00 The neutron diffraction patterns of the three materials are refined, for NVOPF-Li x In the (0 ≤ x ≤ 1.00) sample, a significant change in sodium atom sites was observed after lithium substitution. In the original NVOPF, sodium occupies two distinct sites: fully occupied Na1 sites and partially occupied Na2 sites. At lower lithium substitution levels (0 ≤ x ≤ 0.50), it preferentially occupies the Na1 sites. Subsequently, at higher lithium substitution levels (0.50 < x ≤ 1.00), it occupies the Na2 sites. For NVOPF-Li 0.50 Because lithium and sodium have different neutron scattering lengths, the peak intensity in their neutron diffraction patterns is enhanced. For NVOPF-Li 1.00 The appearance of superlattice peaks with further increases in Li substitution indicates an ordered rearrangement of lithium and sodium. In summary, lithium transitioned from random to ordered occupancy, and this change in occupancy inevitably affects the Na+ content of the material. + The diffusion kinetics properties, in turn, affect the electrochemical behavior.

[0028] Figure 5-7 The NVOPF and NVOPF-Li prepared in this embodiment 0.50 and NVOPF-Li 1.00SEM images of the three materials clearly show that lithium substitution modulates the surface morphology of the samples. The original NVOPF consists of randomly dispersed nanoparticles. With increasing lithium-ion content, these nanoparticles first self-assemble into micrometer-sized rectangular bulks, and eventually decompose to form nanoparticle aggregates with a natto-like structure. This evolution follows a typical Ostwald ripening mechanism. At low lithium substitution concentrations, lithium-induced lattice distortion and strain provide a significant thermodynamic driving force for particle growth, accelerating the Ostwald ripening process. The dissolution of smaller nanocrystals with higher surface energy promotes crystal growth as the dissolved material diffuses through the matrix and deposits onto larger particles. On the other hand, lithium promotes atomic diffusion and induces the directional attachment of primary nanocrystals, leading to a significant increase in particle size. The system minimizes its total energy by dispersing strain over a larger volume. However, above the critical substitution concentration, the accumulated strain energy exceeds the elastic limit of the lattice, triggering a transition from elastic to plastic deformation and forming disordered regions. These disordered regions act as effective crystal growth inhibitors, promoting uniform secondary nucleation and leading to the reformation of smaller particles. Furthermore, at high lithium contents, the reduction of sodium pillars in the original framework results in thermodynamic instability and structural degradation, ultimately producing the observed natto-like morphology.

[0029] The carbon-free coated NVOPF and NVOPF-Li prepared in this embodiment 0.50 and NVOPF-Li 1.00 The material is used as a positive electrode material in sodium-ion batteries, and the specific implementation method is as follows: The aforementioned lithium-substituted sodium vanadium fluorophosphate material was used as the positive electrode active material and ground with conductive carbon black and sodium carboxymethyl cellulose at a mass ratio of 7:2:1. Deionized water was added to the resulting mixture as a solvent to prepare a slurry with uniform viscosity (slurry solid content approximately 20-25 wt%). The slurry was then uniformly coated onto a carbon-coated aluminum foil current collector to form a positive electrode sheet, and then a coin cell was assembled using metallic sodium as the negative electrode. A 1 M NaPF6 diethylene glycol dimethyl ether solution was used as the electrolyte, and charge-discharge tests were conducted at a 1C rate.

[0030] Figure 8 For NVOPF, NVOPF-Li 0.50 and NVOPF-Li 1.00 Constant current charge-discharge curves of the cathode materials. Among them, NVOPF exhibits two distinct voltage plateaus (approximately 3.6 V and approximately 4.0 V), while NVOPF-Li... 0.50 and NVOPF-Li 1.00 It then has an additional low-voltage plateau (approximately 3.4 V). Compared to NVOPF and NVOPF-Li 1.00 NVOPF-Li0.50 It provides 127.2 mAh·g at 1C. -1 High discharge specific capacity, and in the high voltage region (>3.7 V, 66.25 mAh·g) -1 ) and the medium voltage region (3.5-3.7 V, 43.40 mAh·g) -1 Both provide higher discharge capacity, while the low voltage region (<3.5 V) has almost no effect on the overall average operating voltage.

[0031] like Figure 9 As shown, for NVOPF, NVOPF-Li 0.50 and NVOPF-Li 1.00 The cathode material was tested for rate performance at current densities of 1C, 2C, 5C, 10C, 15C, 20C, 30C, 50C, 80C, and 100C. Among them, NVOPF-Li... 0.50 The discharge specific capacity of the positive electrode is 127.2 mAh·g. -1 125.8 mAh·g -1 122.3 mAh·g -1 119.1 mAh·g -1 117.0mAh·g -1 115.3 mAh·g -1 112.5 mAh·g -1 107.7 mAh·g -1 100.4 mAh·g -1 and 94.1 mAh·g -1 When the current density returns to 1C, the discharge specific capacity is 127.1 mAh·g. -1 It exhibits the best rate performance.

[0032] Finally, the NVOPF and NVOPF-Li prepared in Example 1 were also analyzed. 0.50 and NVOPF-Li 1.00 The cathode material underwent long-cycle performance testing at 20°C. For example... Figure 10 As shown, compared to NVOPF and NVOPF-Li 1.00 NVOPF-Li 0.50 The battery's first-week discharge specific capacity was measured to be 113.3 mAh·g. -1 After 25,000 cycles, it provides a discharge specific capacity of 99.5 mAh·g. -1 The capacity retention rate was 87.8%, demonstrating outstanding cycle stability.

[0033] In summary, this invention employs a rapid, low-cost, and scalable microwave hydrothermal assisted calcination method to replace lithium at sodium sites, obtaining a series of carbon-free lithium-substituted sodium vanadium fluorophosphate (NVOPF) materials. Analysis of the phase changes, morphological changes, and electrochemical properties of these materials reveals that replacing lithium at the sodium sites of NVOPF can further improve the electronic conductivity and Na+ of the materials. + The diffusion rate enables the material to achieve excellent rate performance, long cycling performance, and sodium storage capacity. Among them, NVOPF-Li, which simultaneously possesses a micro / nano-scale structure... 0.50 The particles possess both high compaction density and rapid Na content. + Its transport dynamics and excellent structural stability exhibit outstanding rate performance and long-cycle performance, and it also has the best sodium storage capacity.

[0034] The embodiments of the present invention have been described in detail above, but the present invention is not limited to the described embodiments. For those skilled in the art, various changes, modifications, substitutions, and variations can be made to these embodiments without departing from the principles and spirit of the present invention, and these variations still fall within the protection scope of the present invention.

Claims

1. A method for preparing a lithium-substituted sodium vanadium fluorophosphate material, characterized in that, Includes the following steps: S1. Vanadium acetylacetonate is dissolved in ethanol to prepare a vanadium acetylacetonate solution. Sodium dihydrogen phosphate, sodium fluoride, and lithium fluoride are dissolved in water to prepare a mixed solution. The two solutions are then combined to obtain a premixed solution. The mass ratio of vanadium acetylacetonate to ammonium dihydrogen phosphate, sodium fluoride, and lithium fluoride is 175-195:110-130:49.1x:x, where 0 < x ≤ 1.

00. S2. After the premixed liquid of S1 is subjected to microwave hydrothermal reaction, the obtained reaction precursor is placed in an inert gas atmosphere for heat treatment to obtain lithium-substituted sodium vanadium fluorophosphate material.

2. The method for preparing a lithium-substituted sodium vanadium fluorophosphate material according to claim 1, characterized in that, The mass ratio of the acetylacetonate vanadium oxide to ammonium dihydrogen phosphate, sodium fluoride, and lithium fluoride is 180-190:116-125:49.1x:x, where x=0.

5.

3. The method for preparing a lithium-substituted sodium vanadium fluorophosphate material according to claim 1, characterized in that, The microwave hydrothermal reaction is carried out by heating to 120-140℃ at a heating rate of 7-13℃ / min under a microwave power of 300-500 W, and reacting at this temperature for 1-3 hours.

4. The method for preparing a lithium-substituted sodium vanadium fluorophosphate material according to claim 1, characterized in that, The heat treatment is performed at a temperature of 500-700℃ for 6-8 hours.

5. The method for preparing a lithium-substituted sodium vanadium fluorophosphate material according to claim 1, characterized in that, The microwave hydrothermal reaction is carried out under continuous stirring at a speed of 200-400 r / min.

6. The method for preparing a lithium-substituted sodium vanadium fluorophosphate material according to claim 1, characterized in that, The microwave hydrothermal reaction further includes washing and drying steps; the washing involves centrifuging the reaction product with water and ethanol respectively to remove impurities; the drying involves drying the centrifuged precipitate.

7. The method for preparing a lithium-substituted sodium vanadium fluorophosphate material according to claim 6, characterized in that, The centrifugal cleaning speed shall not be less than 6000 r / min.

8. A lithium-substituted sodium vanadium fluorophosphate material prepared by the preparation method according to any one of claims 1-7.

9. The application of the lithium-substituted sodium vanadium fluorophosphate material of claim 8 as a positive electrode active material in the preparation of sodium-ion batteries.

10. The application according to claim 9, characterized in that, The method for using the lithium-substituted sodium fluorophosphate vanadium oxyfluoride material to prepare sodium-ion batteries is as follows: the lithium-substituted sodium fluorophosphate vanadium oxyfluoride material, conductive agent and binder are ground and mixed in a mass ratio of 6-8:1-3:0.5-1.5, and a solvent is added to the mixture to prepare an electrode slurry with uniform viscosity; the slurry is uniformly coated on a conductive current collector to obtain a positive electrode, a sodium-based negative electrode is used, and sodium-ion battery electrolyte is injected to assemble a coin cell sodium-ion battery.